GUAM AND THE SMALLER GAME IN THE POST-SOVIET EXPANSE - SILAEV, Nikolai (CENTRAL ASIA AND THE CAUCASUS, 2006)
The recent political transformations in the post-Soviet expanse are often described as a “Big Game,” meaning a confrontation among the global actors: America, the EU, and Russia. We are used to hearing about how Russia is being squeezed out of its traditional and “natural” sphere of influence—the former Soviet territory—by the West with the help of pro-Western political groups in the Soviet successor states. It has become commonplace to assert that political freedom and democracy, Western values, and the Western civilizational model have spread across the postSoviet expanse and that they are opposed by Eastern authoritarianism and imperialism. Politically, these two approaches are mutually exclusive; but if assessed in absolute magnitude, disregarding their ideological and emotional aspects, we find that they stem from the same logical basis. I mean that the logic of “Western expansion” and “democratization” describes the Soviet successor states and post-Soviet societies as targets of influence of the largest world actors, rather than entities of international politics with willpower, interests, and strategies of their own. In the event these countries are allowed to retain the “right to remain entities,” their willpower, interests, and strategies are described in an extremely simplified way—as the European choice of ideological conceptions. Both the Russian and Western expert communities tend to perceive only the enlarged view of the postSoviet expanse and more likely than not are unable to discern and analyze the details. In fact, the Big Game paradigm draws us away from a more detailed discussion of the newly independent states’ foreign policies.